The structure and organisation of an Amazonian bird community remains little changed after nearly four decades in Manu National Park. (5th January 2023) - Martínez, Ari E.; Ponciano, José M.; Gomez, Juan P.; Valqui, Thomas; Novoa, Jorge; Antezana, Mariamercedes; Biscarra, Gabriela; Camerlenghi, Ettore; Carnes, Blaine H.; Huayanca Munarriz, Renato; Parra, Eliseo; Plummer, Isabella M.; et al.
Abstract: Documenting patterns of spatiotemporal change in hyper‐diverse communities remains a challenge for tropical ecology yet is increasingly urgent as some long‐term studies have shown major declines in bird communities in undisturbed sites. In 1982, Terborgh et al. quantified the structure and organisation of the bird community in a 97‐ha. plot in southeastern Peru. We revisited the same plot in 2018 using the same methodologies as the original study to evaluate community‐wide changes. Contrary to longitudinal studies of other neotropical bird communities (Tiputini, Manaus, and Panama), we found little change in community structure and organisation, with increases in 5, decreases in 2 and no change in 7 foraging guilds. This apparent stability suggests that large forest reserves such as the Manu National Park, possibly due to regional topographical influences on precipitation, still provide the conditions for establishing refugia from at least some of the effects of global change on bird communities. Abstract : We re‐censused a remote Amazonian bird community after 36 years to evaluate community‐wide changes. Contrary to longitudinal studies of other remote neotropical bird communities documenting major declines, we found little change in structure and organization. This apparent stability suggests that large forest reserves such as Manu National Park, possibly due to regional topographical influences on precipitation, still provide the conditions for establishing refugia from at least some of the effects of global change.